Anti-inflammatory effect of Rhododendron brachycarpum D. Don ex G. Don leaves extract on dermatitis - Jinjoo Kang; YoungJae Kim; Jae-Min Chung; Namkyung Kim; Young-Ae Choi; Eun-Nam Kim; Gil-Saeng Jeong; Sang-Yong Kim; Sang-Hyun Kim (Journal of HerbMed Pharmacology, 2023)
Introduction: Rhododendron brachycarpum D. Don ex G. Don(RbGD) leaves have traditionally been used to treat diabetes, rheumatoid arthritis, hypertension, and skin ailments. Although RbGD leaves are used as a medicinal plant, there is no scientific evidence to support skin treatment. Therefore, the purpose of this study was to look into the anti-inflammatory effect of an ethanolic extract of RbGD on skin disease, specifically atopic dermatitis (AD). Methods: The anti-inflammatory effect of RbGD ethanol leaf extract (RbGDE) on tumor necrosis factor-α (TNF-α)/interferon-γ (IFN-γ)-activated keratinocytes was evaluated using MTT, qPCR, ELISA, and Western blot Procedures. The therapeutic effects of RbGDE were evaluated in vivo inflammatory responses by histological observation, quantitative polymerase chain reaction (qPCR), and ELISA using the 1-chloro-2,4-dinitrobenzene (DNCB)/Dermatophagoides farina extract (DfE)-induced AD-like skin mouse model. Results: RbGDE showed the protective effect against irritating and stimulating substances (H2 O2 and TNF-α/IFN-γ) and inhibited TNF-α/IFN-γ-activated keratinocytes by inhibiting the p38 mitogen-activated protein kinase and nuclear factor-kappa B activation. Furthermore, topical RbGDE treatment reduced the AD features such as thickened skin, erythema, immune cells infiltration (eosinophils and mast cells), and AD-related cytokines (IL-12a, IL-1β, IL-4, and TSLP) in the ear tissues of DNCB/DfE-induced mice. The RbGDE also reduced histamine and immunoglobulins (Igs) levels in the serum, including DfE-specific IgE, total IgE, and IgG2a. Conclusion: RbGD leaf extract had an anti-inflammatory effect on dermatitis by reducing inflammatory mediators, indicating that it might be used to treat skin disease.